3
$\begingroup$

If we take this definition for the gamma function:

$$ \Gamma(\alpha)=\int_{0}^{\infty}x^{\alpha-1}e^{-x}\mathrm dx \ \text{ for } \ \alpha>0,$$

and we substitute $\lambda y$ for $x$. Why do we get: $$\Gamma(\alpha)=\lambda^{\alpha}\int_{0}^{\infty}y^{\alpha-1}e^{-\lambda y}\mathrm dy$$ and not: $$\Gamma(\alpha)=\lambda^{\alpha - 1}\int_{0}^{\infty}y^{\alpha-1}e^{-\lambda y}\mathrm dy$$

See (https://www.probabilitycourse.com/chapter4/4_2_4_Gamma_distribution.php)

$\endgroup$
  • 11
    $\begingroup$ Don't forget about the dy term. $\endgroup$ – Chris Mar 25 '18 at 18:59
15
$\begingroup$

When substituting, $\lambda y = x$ means $\lambda\mathrm dy = \mathrm dx$. That is where the extra $\lambda$ comes from.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.